Considerations about Partners in Dialogue in Cicero’s Paradoxa Stoicorum - Galli, Daniela (Ciceroniana On Line, 2024)
The Paradoxa Stoicorum is a short treatise written by Cicero in the spring of 46 BC focused on six Stoic paradoxa. In this essay Cicero does not limit himself to quoting his Stoic sources: he also applies the Stoic paradoxa to his own Roman world. Therefore, the treatise is rich in allusions and references to Cicero’s Rome. At the time when Cicero was writing the Paradoxa Stoicorum, politics was dominated by the figure of Caesar: in April 46 BC Caesar was appointed dictator for 10 years, and the dictatorship granted him near absolute power in both theory and practice. Some scholars have noted that this treatise is a work of resistance against Caesar’s dominion. The paper analyses one aspect of this anti-Caesarian opposition: since in Cicero’s Paradoxa Stoicorum the discussion of each paradoxon has a dialogical structure and is conceived as a debate between two interlocutors having opposite views on the topic, the article focuses on the choice of these partners-in-dialogue by Cicero, suggesting that they are all figures closely related to Caesar (Clodius, Crassus, Mark Antony) or even Caesar himself.